Pengaruh Sistem Pengukuran Kinerja Stratejik Terhadap Kinerja Manajeria l (Studi Empirik Pada Perusahaan Transportasi di bawah Naungan Kementrian BUMN Di Wilayah Jawa) - Winarsih - (Conference In Business, Accounting, And Management (CBAM), 2015)
This study aims to investigate the effect of strategic performance measurement system on managerial performance that is directly tested through four variables; job relevant information, role ambiguty, role conflict and role overload. This study used the perspec tive of goal setting theory and role theory in explaining inter-variable relationship. Data collected in this survey was primary data from 329 functional managers of state-owned transportation companies under the auspices of Ministry of State Owned Enterprise. Samples were taken using stratified random sampling. Of 329 questionnaires, 264 were used  in this research with respon rate of 80,55%. Da ta analysis was conducted using structural equation models in LISREL 8,5. The result of statistictic test indicated that strategic performance measurement system was, but not significantly, associated with managerial performance. Further findings indicated that strate gic performance measurement system was significantly associated with job relevant information, but no association was found with role ambiguity. However, strategic performance measurement system was significantly assosiated with role conflict and role overload. Furthermore, the result of research test indicated that job relevant information was not associated with role ambiguty, role conflict and role overload, but significantly associated with managerial performance. Based on the result, it can be conferred that role ambiguity was positively related and had a significant impact on managerial performance.   In the other hand, role conflict and role overload are positvely but not significantly assosiated with managerial performance.The result of the role test of mediating variables has shown that job relevant information, role ambiguity, role conflict and role overload significantly mediated the effect of strategic performance measurement system toward managerial performance.  Keywords :  Strategic Performance Measurement System, Job Relevant Information, Role Stress Characteristic and Managerial Performance